LITHOLOGICAL CLASSIFICATION OF DIKES IN THE MALGUZAR MOUNTAINS - ugli, Berkinov Nodirbek Alisher; Atabayev Javlon Tolliboy ugli; Boboyorov Asliddin Akrom ugli (Journal of Geography, Regional Planning and Development, 2024)
Objective: This study aims to provide a detailed geological analysis of the Malguzar Mountains, focusing on the lithological classification of dikes, structural features, and mineral resources within the Southern Tien Shan fold system. Method: A combination of field observations, petrographic analysis, and geochemical studies were employed to classify the dikes and examine their structural characteristics. The research also involved a comprehensive review of the geological history and mineral potential of the region. Results: The Malguzar Mountains are identified as a key structural unit within the Southern Tien Shan fold system, consisting of a large anticlinorium formed by complex Silurian-Devonian rock formations. The study found a diverse range of dike types, with significant variations in composition and mineralization, which have implications for the area's economic geology. Novelty: This research is one of the first to systematically classify dikes in the Malguzar Mountains and analyze their role in the broader tectonic context of the Southern Tien Shan. The findings contribute to understanding the geological framework of the region and offer insights into its mineral resource potential, which may aid future exploration efforts.